(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze and demonstrate the influence of digital marketing, price, and service quality on purchase intention among consumers at a smoked fish processing center in Wonosari Village, Demak Regency. Respondents in this study were 97 consumers at a smoked fish processing center in Wonosari Village, Demak Regency. Data collection was conducted by distributing questionnaires. This study employed quantitative methods using Google Forms. The results of this study indicate a positive and significant effect of digital marketing on purchase intention, price on purchase intention, and service quality on purchase intention. Meanwhile, the F-test showed a significant positive effect between digital marketing (X1), price (X2), and service quality (X3) on purchase intention (Y).